Exogenous auxin-induced ENHANCER OF SHOOT REGENERATION 2 (ESR2) enhances femaleness of cucumber by activating the CsACS2 gene. Issue 1 (20th January 2022) - Niu, Huanhuan; Wang, Hu; Zhao, Bosi; He, Jiao; Yang, Luming; Ma, Xiongfeng; Cao, Jiajian; Li, Zheng; Shen, Junjun
Abstract: Cucumber ( Cucumis sativus L.) has been a model for the study of sex differentiation over the last two decades. Cucumber sex differentiation is mainly under genetic control, but plant growth regulators can also influence or even change it. However, the effect of exogenous auxin application on cucumber sex differentiation is not well understood at the physiological level. In this study, we explored the effects of different exogenous auxin concentrations on cucumber varieties with different mutant sex-controlling genotypes and found that there was a dosage effect of exogenous indole-3-acetic acid (IAA) on the enhancement of cucumber femaleness. Several ACC synthetase (ACS) family members responded directly to exogenous IAA, increasing endogenous ethylene synthesis, and this process appeared to be independent of the previously identified sex-related ACC oxidase CsACO2. We further demonstrated that ENHANCER OF SHOOT REGENERATION 2 (ESR2) responded to exogenous auxin induction by binding to ERE cis -acting element regions in the CsACS2 promoter, directly activating CsACS2 expression and thus increasing endogenous ethylene content, which may induce femaleness. These findings reveal that exogenous auxin increases cucumber femaleness by inducing a sex-controlling gene and promoting ethylene synthesis.